Amphi-functional mesoporous silica nanoparticles for dye separation - Shinde, Pravin; Sen Gupta, Sayam; Singh, Baljeet; Polshettiwar, Vivek; Prasad, Bhagavatula L. V. (Journal of Materials Chemistry A, 2017)
Synthesis of amphi-functional mesoporous silica nanoparticles (similar to 80 nm) by stepwise chemical modifications of outer and inner pore surfaces is reported. These materials display a clear "Janus" like character and are able to selectively and completely separate hydrophobic dyes form a mixture of dyes. Our results clearly suggest a clear partition of more hydrophobic dyes into the pores from a mixture of two dyes. In addition this material displays a remarkable recycling ability for 10 cycles with up to similar to 99% dye removal from water.

Interfacial-active polymer nanoparticles, their assemblies, and SERS application - Visaveliya, Nikunjkumar R.; Li, Xiang; Knauer, Andrea; Prasad, Bhagavatula L. V.; Kohler, Johann Michael (Macromolecular Chemistry and Physics, 2017)
In this work, surface-active polymer nanoparticles as well as polymer-polymer and polymer-metal nanoassembly particles are synthesized, and different parameters such as their size, morphologies, and assembling strength are studied. Nanoassembly particles are attractive because of the coupled properties with a large surface to volume ratio. A key challenge is to produce the core-shell polymer nanoparticles via single-step processes. To address this concern, here, microfluidics approach and precise interfacial reaction strategies are used, and hence different types of surface layered polymer nanoparticles are obtained in one-step processes. An inner core material is hydrophobic, whereas a hydrophilic surface layer (in situ formed during the polymerization process) swells in the aqueous environment. Moreover, three different reaction setups (batch, flow, and in situ) are applied in order to architect the nanoassembling hierarchical structures via layer-by-layer strategy. On the other side, polymer-metal nanoassembly particles as well as metal catalyzed metal deposited four layered nanoassembly particles of tuned size and compositions are produced. It is shown that these particles can be used as nanosensor particles for surface-enhanced Raman spectroscopy.

Micelles versus Ribbons: how congeners drive the self-assembly of acidic sophorolipid biosurfactants - Dhasaiyan, Prabhu; Griel, Patrick Le; Roelants, Sophie; Redant, Emile; Bogaert, Inge N. A. Van; Prevost, Sylvain Francois; Prasad, Bhagavatula L. V.; Baccile, Niki (ChemPhysChem, 2017)
Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congeners with stearic acid (C18:0) or linoleic acid (C18:2) results in the formation of micelles that are stable over long periods of time. Conversely, the presence of only 10 to 15 % of congeners with a stearic acid chain gives fibrillar structures instead of micelles. To study the mechanisms responsible, oleic acid SLs devoid of any other congeners were prepared. Very interestingly, this sample can self-assemble into either micelles or fibers depending on minute modifications to the self-assembly conditions. The findings are supported by light scattering, small-angle X-ray scattering, transmission electron microscopy under cryogenic conditions, high-pressure liquid chromatography, and NMR spectroscopy.

Microwave assisted batch and continuous flow synthesis of palladium supported on magnetic nickel nanocrystals and their evaluation as reusable catalyst - Nikam, Arun V.; Kulkarni, Amol A.; Prasad, Bhagavatula L. V. (Crystal Growth & Design, 2017)
Palladium nanocrystals (NCs) supported on nickel NCs (Pd/Ni) were synthesized in a continuous flow manner by the microwave-assisted method in the presence and absence of oleylamine. Parameters optimized for batch experiments were considered while performing continuous flow synthesis. The Pd/Ni NCs synthesized in the presence of oleylamine displayed good catalytic activity for hydrogenation of aromatic nitro compounds, and those bearing alkene, and alkyne moieties. The ferromagnetic character of the supporting nickel NCs allowed the recovery of the catalyst and these recovered catalysts could be reused several times.

Nanoparticle assembly: a perspective and some unanswered questions - Kumar, Sanat K.; Kumaraswamy, Guruswamy; Prasad, Bhagavatula L. V.; Bandyopadhyaya, Rajdip; Granick, Steve; Gang, Oleg; Manoharan, Vinothan N.; Frenkel, Daan; Kotov, Nicholas A. (Current Science, 2017)
In early 2016, the Royal Society of Chemistry arranged a meeting on the topic 'Nanoparticle Assemblies: from Fundamentals to Applications' which was hosted at IIT-Bombay, Mumbai. The meeting brought several leading nanoscience and nanotechnology researchers to India and is only the second Faraday Discussions meeting to have been held in the country. The papers presented at the meeting and the resulting active discussions have been summarized in a Faraday Discussion issue(1). The broad range of topics discussed at the meeting led to an understanding on where we stand in the field of nanoparticle assembly, and also enunciated some of the outstanding fundamental and practical issues that remain to be resolved before these ideas can be applied to practical situations. Driven by these ideas, here we focus on four topics/questions: (i) Can we achieve function-driven design of nanoparticle assemblies? (ii) What is the minimal information needed to build a desired assembly? (iii) How complex a structure can one build? How can one make it responsive? What are the relative roles of equilibrium versus dynamics in the assembly process, and are we at a point where we can now pursue active assembly as a viable mode for creating complex assemblies? (iv) What are the applications that are being targeted and what are the barriers to implementation? In this perspective, we do not present an exhaustive survey of the vast literature in this area, but indicate overarching themes/questions that require immediate attention, largely based on the discussions at the Mumbai meeting.

Nickel-catalyzed direct synthesis of dialkoxymethane ethers - Subaramanian, Murugan; Bera, Abhijit; Prasad, Bhagavatula L. V.; Balaraman, Ekambaram (Journal of Chemical Sciences, 2017)
A simple and efficient method for the preparation of dialkoxymethane ethers (oxymethylene ethers) from alcohols and paraformaldehyde in the presence of commercially available nickel(II) salt is described. The reaction proceeds readily under neutral, solvent-free conditions using paraformaldehyde as a C-1 source. The present strategy has a broad substrate scope including aliphatic (both primary and secondary) and aromatic alcohols and provides a benign method for the preparation of symmetrical dialkoxymethanes in good yields (up to 89%).

2D molecular precursor for a one-pot synthesis of semiconducting metal sulphide nanocrystals - Bera, Abhijit; Prasad, Bhagavatula L. V. (Bulletin of Materials Science, 2018)
2D molecular materials, namely, metal alkyl thiolates, have been used as a single-source precursor for the synthesis of semiconducting metal sulphide nanocrystals (NCs) by thermal decomposition. These 2D molecular precursors have all the ingredients required for metal sulphide synthesis (metal source, sulphur source and protecting ligand). In this study, we demonstrate a simple and general solvothermal decomposition' approach for the synthesis of high-quality , PbS, CdS, MnS and ZnS NCs. The size of the NC can also be controlled by changing the decomposition temperature. Furthermore, the optical properties of the NCs have also been studied.

Ligand-solvent compatibility: the unsung hero in the digestive ripening story - Shimpi, Jayesh R.; Chaudhari, Vijay Raman; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Digestive ripening (DR) is a process where a polydisperse nanocrystal (NC) system is converted into a monodisperse one with the aid of thermal heating of NCs in the presence of an excess surface-active organic ligand called digestive ripening agent (DRA) and a solvent. Here, we demonstrate that the solvent-DRA compatibility influences the final size and size distribution of the NCs in a significant manner. Accordingly, in this study, using the DR of gold NCs as the test case with alkanethiol (decanethiol/C10HT) and fluorinated thiol (1H,1H,2H,2H-perfluorodecanethiol/C10FT) as DRA's and toluene and alpha,alpha,alpha-trifluoro-toluene (TFT) and their combination as solvents, we clearly establish that alkanethiols result in best-quality NCs after DR in toluene while the fluorinated thiols provide reasonably monodispersed NCs in TFT. Our results also ascertain that even when DR is carried out in a mixture of solvents, as long as the compatible solvent is the major component, the DR process results in reasonably monodisperse NCs. As soon as the amount of uncompatible solvent exceeds a threshold limit, there is perceptible increase in the polydispersity of the NCs. We conclude that the polarity of the solvent, which affects the buildup of ligated atoms/clusters, plays a key role in controlling the size distributions of the NCs.

pH- and time-resolved in situ SAXS study of self-assembled twisted ribbons formed by elaidic acid sophorolipids - Dhasaiyan, Prabhu; Prevost, Sylvain; Baccile, Niki; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Conditions that favor the helical structure formation in structurally similar sophorolipids (SLs), that is, elaidic acid SLs (having a trans double bond between the C9 and C10 positions of the alkyl chain) and stearic acid SLs (no double bond), are presented here. The helical self-assembled structures formed by elaidic acid SLs were independent of pH and also were mediated by a micellar intermediate. On the other hand, the stearic acid SLs formed helical structures under low pH condition only. Astonishingly, the formation routes were found to be different, albeit the molecular geometry of both SLs is similar. Even if a conclusive mechanistic understanding must await further work, our studies strongly point out that the noncovalent weak interactions in elaidic acid SLs are able to overcome the electrostatic repulsions of the sophorolipid carboxylate groups at basic pH and facilitating the formation of helical structures. On the other hand, the hydrophobic interactions in stearic acid SLs endow the helical structures with extra stability, making them less vulnerable to dissolution upon heating.

Preparation of metal oxide supported catalysts and their utilization for understanding the effect of a support on the catalytic activity - Seth, Jhumur; Dubey, Prashant; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2018)
A convenient way of anchoring transition metal nanoparticles (palladium, platinum, rhodium and ruthenium) onto metal oxide supports (magnesium oxide and zirconium oxide) by means of a modified sol-gel technique is demonstrated. Use of toluene dispersed, ligand protected pre-synthesized nanoparticles during sol-gel synthesis delivered size-controlled, spatially distributed, well-adhered transition metal nanoparticles (MNPs) on metal oxide supports. The catalytic activities of these supported nanoparticles were tested for the p-nitro phenol reduction reaction. It was observed that the reaction kinetics were crucially dependent on the catalyst support and MNP size. The influence of the magnesium oxide and zirconium oxide supports towards the catalytic performance of the anchored transition MNPs was probed using cyclic voltammetry and the differences in the same were attributed to the support-induced modification in the electronic properties of the MNPs. Our results indicated that magnesium oxide is a better support than zirconium oxide.

Mechanistic aspects of methanol electro-oxidation reaction through cyclic voltammetry: is it correct to blame carbon monoxide for catalyst poisoning? - Deshpande, Pooja S.; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (Energy Technology, 2020)
The mechanism of the methanol oxidation reaction is revisited using systematic cyclic voltammetric studies. These studies clearly indicate that the peak during the cathodic scan belongs mainly to electro-oxidation of the carbon monoxide, and that only a fraction of this carbon monoxide remains adsorbed on the electrode, contrary to what previous reports suggested. More details can be found in article number by Bhagavatula L. V. Prasad and co-workers.
Keywords: carbon monoxide; cyclic voltammetry; electrocatalysts; electrode poisoning; Methanol oxidation

Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals (vol 6, pg 12006, 2018) - Bera, Abhijit; Busupalli, Balanagulu; Prasad, Bhagavatula L. V. (ACS Sustainable Chemistry & Engineering, 2020)

Selective electro-oxidation of phenol to 1,4-hydroquinone employing carbonaceous electrodes: surface modification is the key - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2022)
The oxidation of phenol leading to 1,4-hydroquinone with high conversion, remarkable selectivity and an excellent yield (87% isolated) has been accomplished under electrolytic conditions in an aqueous medium employing carbon-based electrodes. To achieve this, various factors such as electrode stability, repeatability, and the type of product formed by the electrochemical oxidation of phenol have been investigated using cyclic voltammetry first and then organic transformations under optimized conditions were accomplished by constant current electrolysis. The voltammetric data clearly show that electrochemically generated intermediates passivate the surface of the typically used electrodes, leading to a decrease in their activity, which is a major problem concerning the transformation of phenol electro-oxidation to an industrially adaptable process. In this work, it is established that such difficulties could be circumvented using surface modified carbonaceous electrodes having disordered graphene-like structures and oxygen functional groups. It is also demonstrated that surface modified reticulated vitreous carbon (RVC) based electrodes could be used for electro-oxidation of phenol at a reasonably large scale. The electrolysis conditions have been optimized based on the mechanistic understanding leading to remarkable conversion of phenol with 87% selectivity to 1,4-hydroquinone.

Alloying with Mn enhances the activity and durability of the CoPt catalyst toward the methanol oxidation reaction - Deshpande, Pooja; Prasad, Bhagavatula L. V. (ACS Applied Materials & Interfaces, 2023)
To improve the catalytic performance and durability ofPt catalystsused for the methanol oxidation reaction (MOR) in direct methanolfuel cells (DMFCs), alloying of Pt with other transition metals suchas Ru, Co, Ni, and Fe is considered an effective approach. Despitethe significant progress made in the preparation of bimetallic alloysand their utilization for MOR, improving the activity and durabilityof the catalysts to make them commercially viable remains a stiffchallenge. In this work, trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts were successfully synthesized via borohydridereduction followed by hydrothermal treatment at 150 & DEG;C. The electrocatalyticperformance of the synthesized trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts toward MOR was studied using cyclicvoltammetry and chronoamperometry. The results affirm that all Pt100-x (MnCo)( x ) (16 < x < 41) alloys have superior MOR activityand durability as compared to bimetallic PtCo alloys and commerciallyavailable Pt/C (comm. Pt/C) catalysts. Among all the compositionsstudied, the Pt60Mn1.7Co38.3/C catalystexhibited superior mass activity (1.3 and 1.9 times higher than thoseof Pt81Co19/C and comm. Pt/C, respectively)toward MOR. Furthermore, all the newly synthesized Pt100-x (MnCo)( x )/C (16 < x < 41) catalysts showed better CO tolerance when comparedwith comm. Pt/C. This improved performance of the Pt100-x (MnCo)( x )/C (16 < x < 41) catalyst can be attributed to the synergisticeffect of Co and Mn on the Pt lattice.
Keywords: CO tolerance; direct methanol fuel cells; electrocatalysis; methanol oxidation reaction(MOR); trimetallic alloy catalysts

Influence of van der waals interactions between the alkyl chains of surface ligands on the size and size distribution of nanocrystals prepared by the digestive ripening process - Shimpi, Jayesh R.; Thomas, Rinto; Meena, Santosh Kumar; Prasad, Bhagavatula L. V. (Langmuir, 2023)
Thermal heating of polydispersed nanocrystals (NCs) with surface-active organic ligands in a solvent leads to the formation of monodispersed NCs, and this process is known as digestive ripening (DR). Here, by performing DR on Au NCs using different-chain-length amine and thiol ligands, we evidently show that ligands with C-12 chain length result in the formation of NCs with narrow size distributions when compared to C-8, C-16, and C-20 chain length ligands. Furthermore, our findings also show that in the case of alkyl thiol, the NC size remains more or less the same, while the size distribution gets altered significantly with the chain length. On the other hand, both size and size distribution are affected significantly when the alkyl amine chain length is varied. Fourier transform infrared (FTIR) studies indicate that the van der Waals (vdW) interactions are weakest when the amine with C-12 carbon chain is used as the DR agent, while in the case of thiols, molecules with C-8 and C-12 chain lengths have nearly the same vdW interactions (with C-12 slightly weaker than C-8), which are weaker than those of C-16 and C-20. Molecular dynamics (MD) simulation results corroborate the experimental observations and suggest that due to more defects in the alkyl chain, the C-8 and C-12 (amine as well as thiol) ligands are disordered and less stable on Au(111) and Au(100) surfaces. This could result in efficient etching and redeposition, making the ligands with C-8 and C-12 chain lengths the better DR agents.

Surface functionalization of inorganic nanoparticles with ligands: a necessary step for their utility - Bhattacharjee, Kaustav; Prasad, Bhagavatula L. V. (Chemical Society Reviews, 2023)
The importance of organic ligands in protecting inorganic nanoparticles and thus imparting the needed stabilization as colloidal dispersions was realised many years ago. Currently, the rational preparation of such nanoparticles with designed organic molecules/ligands resulting in the formation of functional nanoparticles (FNPs) that are tuned for a specific application is an area of immense research interest. The preparation of such FNPs for a desired application requires a clear understanding of the interactions at the nanoparticle (NP)-ligand and ligand-solvent interfaces, and demands a deep appreciation of the surface science and coordination chemistry. In this tutorial review, we briefly explore the evolution of surface-ligand chemistry and inform the readers that, apart from protecting the surface, ligands can modulate the physico-chemical properties of the underlying inorganic NPs as well. This review further presents the design principles for the rational preparation of such FNPs, where one or more ligand shells can be added to the nanoparticle surface, thereby improving the adaptability and amenability of the NP exterior towards the environment in which they are present, as required for a specific application.

Topological phases in nanoparticle monolayers: can crystalline, hexatic, and isotropic-fluid phases coexist in the same monolayer? - Bhattacharjee, Kaustav; Vaidya, Salil S.; Pathak, Tushar; Shimpi, Jayesh R.; Prasad, Bhagavatula L. V. (Soft Matter, 2023)
Topological phases are stable configurations of matter in 2-dimensions (2D) formed via spontaneous symmetry breaking. These play a crucial role in determining the system properties. Though a number of fundamental studies on topological phase transitions and topological defect dynamics have been conducted with model colloidal systems (typically microns in size), the same is lacking on nanoparticle monolayers (NPMLs, typically made of ligand-coated sub-ten nanometer particles). Here, we show that in an evaporation-driven self-assembly process, the three topological phases, namely crystalline, hexatic, and isotropic-fluid phases, can coexist within the same NPML. We associate this coexistence with the local variation in particle size, which can be described by a unique frequency parameter (p(25)), quantifying the fraction of NPs that has size deviation greater than or equal to 25% of the mean size (where the deviation,f is defined as f = ((|Size-mean|)/mean)). The p(25)-values for the three phases are distinctly different: crystalline arrangement occurs when p(25) < similar to 0.02, while a hexatic phase exists for 0.02 <= p(25) <= 0.1. For p(25) Z 0.1, the isotropic-fluid phase occurs. Following KTHNY-theory, we further numerically extrapolate the occurrence of each phase to the accumulated excess planar strain in the NPML due to the presence of various topological defects in the structures.

Continuous flow synthesis of mesoporous silica particles with tunable size and structure - Jundale, Rajashri B.; Prasad, Bhagavatula L. V.; Devi, R. Nandini; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
We have developed a continuous process to prepare mesoporous silica particles of different sizes and narrow size distribution in a tubular reactor. The method is based on the use of well-known Stober synthesis in the presence of cationic surfactant in methanol-water solvent system and trimethylbenzene as pore swelling agent to form porous silica particles. We observed that reaction parameters had enormous effects on particle size, distribution, and numerous morphological aspects. We demonstrated that these properties may be modified by adjusting the reaction temperature, base concentration, and surfactant concentration. MSPs of spherical morphology with variable size from 400 to 1000 nm produced with the surface area >600 m(2)/g and pore diameter of 2-4 nm. Large scale production is demonstrated by increasing reactor volume using 1/4 in. PTFE tubing from 20 to 163 mL, with this production of MSPs increased from 0.35 to 3 g/h. The method has been extended for high yield production at the kilogram scale using this approach, which will pave the way toward the industrialization of mesoporous silica based materials.

Electrodeposited Co-Mn-Sn multicomponent alloy as an efficient electrocatalyst for hydrogen evolution reaction - Chandran, M. Athira; Karumuthil, Subash Cherumannil; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (International Journal of Hydrogen Energy, 2024)
Despite having exciting material characteristics, the potential of multi-component alloys (MCAs) as electrocatalysts has not been fully realized. In this work, efficient binary and ternary MCA electrocatalysts containing inexpensive metals like Co, Mn and Sn have been prepared via the electrodeposition process. When tested for hydrogen evolution reaction (HER) in an alkaline medium, ternary Co-Mn-Sn alloy displayed enhanced activity with the lowest overpotential of 136 mV, a Tafel slope of 111 mV dec 1 and a very low charge transfer resistance, making it superior to the binary alloys (Co-Mn and Co-Sn), or the single metal catalysts (Co, Mn and Sn). The ternary alloy also displayed high electro-chemical and structural stability, making it a viable electrocatalyst for the hydrogen economy.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean energy; electrocatalysis; Electrodeposition; hydrogen evolution reaction; Multi-component alloy; Non-platinum group metals

Establishing a new efficiency descriptor for methanol oxidation reaction and its validation with commercially available Pt-based catalysts - Deshpande, Pooja S.; Radhakrishnan, Thulasi; Prasad, Bhagavatula L. V. (Fuel Cells, 2024)
Direct methanol fuel cells (DMFCs) have received a lot of attention in recent years as promising technology for generating clean and efficient energy. In DMFC, the anode catalyst is a vital component because it is involved in the oxidation of methanol, which produces electrons that can be used as an energy source. Cyclic voltammetry (CV) is commonly used to test the characteristics of the electrode materials before they are employed in the actual fuel cell. Interestingly in the case of DMFCs CV also is a useful technique to obtain vital information about the performance and expected efficiency of the electrodes. In general, the CV of methanol electrooxidation for Pt-based catalysts has two peaks, If in the forward scan (anodic scan) and Ib in the backward scan (cathodic scan). The ratio of these two peaks (If/Ib) is the most commonly used criterion for investigating CO poisoning in catalysts. However, there is a great deal of ambiguity surrounding this criterion, owing to the genesis of Ib. Addressing this we present here a new criterion to evaluate the efficiency of the catalyst using the same CV technique. We validate this newly proposed criterion with commercial Pt/C (comm. Pt/C) and other commercially available alloy catalysts.
Keywords: catalyst poisoning; CO tolerance; direct methanol fuel cells; electrocatalysis; Methanol oxidation reaction

One-pot, easy and scalable synthesis of large-size short wave length IR emitting PbS quantum dots - Sahu, Umasharan; Prasad, Bhagavatula L. V. (Photochemistry and Photobiology, 2024)
This study presents a versatile and efficient method to synthesize large-size lead sulfide (PbS) quantum dots (QDs) that display emission in the short-wave infrared (SWIR) region, using accessible and stable diethylammonium diethyldithiocarbamate (C-2)(2)DTCA and octylammonium octyldithiocarbamate (C(8)DTCA) as sulfur sources. As these sulfur sources enable the formation of well-dispersed, large-size PbS QDs in a very convenient way, this method can further be taken up for scale-up studies. Importantly, this approach allows precise control over QD sizes, thereby enhancing their SWIR optical properties. By adjusting the hot injection temperatures and sulfur source concentrations, different synthesis routes are explored, providing flexibility for the desired QD characteristics. The results presented here offer a promising opportunity to leverage the synthesized PbS QDs in applications such as optoelectronics, sensors, and imaging technology.
Keywords: hot injection method; Optical properties; quantum dots; short wave IR emission

Polymer nanocomposites with UiO-derived zirconia fillers for energy generation and pressure-sensing devices: the role of crystal structure and surface characteristics - Mukherjee, Gargi; Verma, Ankur; Madhu, Arjun Hari; Prasad, Bhagavatula L. V.; Karumuthil, Subash Cherumannil (ACS Applied Nano Materials, 2024)
Piezoelectric energy harvesting and pressure sensing using polymer nanocomposites have opened up promising avenues in the field of flexible electronics. Herein, the influence of varying crystal structures of zirconia nanoparticles on a piezoelectric energy-generating zirconia-poly(vinylidene difluoride) (PVDF) composite is investigated, and the fabrication of a security alert pavement unit using the material with an optimized composition is demonstrated. More specifically, two metal-organic frameworks, UiO-66 and UiO-67, were employed to synthesize four different types of zirconia nanoparticles with precise control of the monoclinic and tetragonal phases. Polymer nanocomposite with monoclinic zirconia nanoparticles derived from UiO-66 (ZrO2-66m) performed better than other derivatives with 61% enhancement in the beta phase with respect to pure PVDF. It was hypothesized that the stable crystalline structure of the monoclinic phase might act as a better nucleating agent, and among monoclinic derivatives, ZrO2-66m was found to be more hydrophobic, probably enabling a better interaction with PVDF. Subsequently, a prototype device with a PVDF-ZrO2-66m (P/66m) film was made and tested for its energy generation. The maximum output voltage generated by the device under an irregular biomechanical hand tapping force of 8-9 N was 80 V, while the maximum open circuit current was found to be 65 mu A. The prototype displayed a power of 2162.24 mu W at a load resistance of 1 M Omega. A laboratory scale demonstration was executed with the prototype as an energy-generating and security alert pavement unit. A wireless, Bluetooth-based security alert system supported by an Android application was developed and demonstrated as a promising application with the fabricated prototype. The results and demonstrations validate that the PVDF-monoclinic ZrO2 nanoparticle nanocomposites will be an excellent value addition for flexible, durable energy generation and pressure-sensing applications.
Keywords: energy generation and pressure sensing; piezoelectric materials; PVDF/ZrO2 polymernanocomposite; self-powered devices; wearable electronics

Design and synthesis of PtPdNiCoMn high-entropy alloy electrocatalyst for enhanced alkaline hydrogen evolution reaction: a theoretically supported predictive design approach - Chandran, M. Athira; Dutta, Pritha; Singh, Prashant; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (Advanced Functional Materials, 2025)
Electrocatalytic hydrogen generation requires a cutting-edge, multifunctional electrocatalyst with abundant active sites to drive multielectron transfer reactions. High entropy alloys (HEA) are complex five or more-element alloy systems with high configurational entropy which makes them unique materials for next-generation electrocatalysts. Here, in this work, based on new screening guidelines for catalyst selections that combine density-functional theory calculated Gibbs formation-enthalpy with bond length and electronegativity variance, a novel HEA electrocatalyst consisting of five elements, namely, Pt, Pd, Ni, Co, and Mn is designed. By simple room temperature electrodeposition, the designed catalyst is prepared and its hydrogen evolution reaction (HER) is explored and validated through experimental and theoretical approaches. The HEA demonstrated a superior HER activity with an overpotential of 22.6 mV at -10 mA cm-2 which outperforms Pt/C commercial catalyst. No evident degradation of the material is detected even after 100 hours of continuous operation under high current density. Moreover, the HEA has shown exceptional performance in harsh electrolyte conditions such as in simulated seawater and actual seawater. Remarkably, the density-functional theory calculated small Gibbs formation-enthalpy (approximate to 0 eV) compared to Pt/C places the new HEA near the apex of Trasatti's model of Volcano plot, which is also suggestive of superior HER activity.
Keywords: DFT; electrocatalysts; Electronic Structure; HER; high-entropy alloys

An effective alliance for successful coupling: electrochemical alcohol oxidation mediated conversion of indoles to bis(indolyl)methanes - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (Journal of Applied Electrochemistry, 2025)
Electro-organic transformation of indoles to bis(indolyl)methanes (BIMs) has been successfully achieved by combining the electrochemical alcohol oxidation reaction (AOR) with indole coupling. The fact that it is the readily available alcohols and not the traditionally used aldehydes or ketones that provide the bridging -CH2- (methylene) for this transformation makes this path extremely attractive and valuable. The formation of aldehydes as reactive intermediates during the AOR has been dexterously utilized to achieve this transformation. Most gratifyingly, the transformation also can be carried out in water-alcohol mixtures and the yields and conversions are better than the most of the previously reported chemical catalytic transformations using specially designed metal complexes. Various substituted indoles were selectively converted to their corresponding BIMs in decent yields. This strategy could further be exploited for the synthesis of different natural products, including the much sought after deuterium substituted ones (as CD3OD is readily accessible), and other important biologically active alkaloids and drug molecules, etc.
Keywords: Alcohol oxidation reaction; Bis(indolyl)methanes; Direct alcohol fuel cell; Electroorganic transformations; Vibrindole A

Platinum-free electrocatalysts based on electrodeposited Co-Mn-Ni alloys for efficient electrocatalytic alkaline water splitting - Chandran, M. Athira; Dutta, Pritha; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (ACS Applied Energy Materials, 2025)
The development of a Pt-free electrocatalyst for efficient and stable water splitting is crucial for the commercialization of green hydrogen production. A low-cost electrocatalyst with good hydrogen and oxygen evolution activities (HER and OER, respectively) displaying long durability is the first step in this direction, and if the catalyst can be synthesized via an easy, convenient, and scalable procedure, that would be an added advantage. Multicomponent alloys, with their tunable compositions and abundant active sites, present a promising solution in this direction. Herein, a cost-effective CoMnNi (CMN) alloy is synthesized via electrodeposition and with optimized composition by tuning the electrolyte concentration and deposition potential to enhance electrocatalytic performance. The resulting single-phase alloy exhibits a high electrochemical surface area with an average particle size of similar to 4 nm, demonstrating excellent hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities in 1 M KOH, with overpotentials of 121 mV at -10 mA cm-2 and 285 mV at 20 mA cm-2, respectively. Moreover, the catalyst exhibits remarkable stability, sustaining 100 h of operation at 100 mA cm-2. The CMN alloy also performs efficiently under harsh conditions, including 6 M KOH and alkaline seawater, in both symmetric and asymmetric cell configurations. This work highlights the potential of multicomponent alloys as durable, high-performance electrocatalysts for scalable water splitting, paving the way for sustainable hydrogen production.
Keywords: alkaline seawater; electrocatalysis; Electrodeposition; hydrogen evolution reaction(HER); multicomponentalloy; oxygen evolution reaction (OER); stability; watersplitting

Strategic design of a single-source precursor for in situ generation and integration of adherent species on Ni3S4 entangled-nanosheets for energy storage applications - Singh, Rahul; Thakur, Rohit; Sahu, Umasharan; Sahoo, Ramesh Chandra; Prasad, Bhagavatula L. V.; Matte, H. S. S. Ramakrishna (ACS Applied Nano Materials, 2025)
Synthesizing transition-metal chalcogenides (TMC) via a single-source precursor (SSP) route has shown great potential due to better reproducibility and control over stoichiometry, phase, and morphology. While the SSP converts into TMC, surfactants or coordinating species are essential to ensure dispersibility for further solution-based processing protocols. These additional species are typically highly toxic, difficult to remove, and adversely affect device performance. Here, as a proof of concept, design-induced in situ stabilized Ni3S4 (DiSNi) protocol demonstrates that strategic SSP design and optimized reaction conditions can facilitate directed chemical reactivity, gradually generating adhering species, which seamlessly integrate onto the metal chalcogenides, aiding the formation of stable dispersions without utilizing additional stabilizers. The proposed mechanism is validated by detailed strategic experiments and analysis, like X-ray photoelectron spectroscopy (XPS), accelerated dispersion stability measurements, and postsynthesis base treatment, which confirm the presence of in situ generated diethylammonium ion (DEA+) as the adherent and corroborate its role in dispersibility. The obtained Ni3S4 entangled-nanosheets are utilized to fabricate additive-free symmetric supercapacitors with organic electrolyte for charge storage over an extended potential window of 2.8 V and an energy density of 12.44 mu W h cm-2 at a power density of 0.42 mW cm-2. The devised DiSNi protocol showcases the importance of the SSP design for achieving multifunctionality. It is anticipated to have a broader impact on the role of careful design of SSP, making it an ideal contender for synthesizing transition-metal chalcogenides.
Keywords: dispersion stability; energy storages devices; low-boiling point solvents; nickel sulfide dispersions; organic electrolyte; single-source precursor; Supercapacitors

Synthesis framework for designing PtPdCoNiMn high-entropy alloy: a stable electrocatalyst for enhanced alkaline hydrogen evolution reaction - Chandran, M. Athira; Sahoo, Sudeshna; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (Small, 2025)
High entropy alloys (HEAs) are an emerging class of advanced materials characterized by their multifunctionality and potential to replace commercial catalysts in electrocatalytic water splitting. The synergy among the various alloyed elements in HEAs makes them particularly promising for applications in electrocatalysis. However, preparation of HEA via bottom-up approaches by avoiding the formation of mono, di, and tri metallic alloys in the nanoscale is challenging. This aspect is addressed, in this study by exploring the logical selection of solvents, reducing agents, and capping agents, along with their relative fractions, in the solvothermal synthesis of the HEA comprising platinum-palladium-cobalt-nickel-manganese (PtPdCoNiMn). It is established that the reducing capabilities of both the solvent and reducing agent are crucial for the reduction of each metal to form a single-phase HEA. The synthesized HEA (20 wt.%)/functionalized carbon (FC) demonstrates excellent performance as an HER catalyst, exhibiting a low overpotential of 48.7 mV at -10 mA cm-2 in an alkaline electrolyte. This performance is characterized by high reaction kinetics and stability at elevated current densities. Furthermore, the catalyst shows impressive performance in both simulated and actual seawater. This development reduces the reliance on platinum while enhancing the long-term durability and catalytic efficiency of the electrocatalyst.
Keywords: electrocatalysts; HER; high entropy alloys; solvothermal synthesis

Tailoring of rheological properties through hydrophobic interactions in silica-based liquid crystal gels - Sumana, S.; Chakrabortty, Pratyasha; Karumuthil, Subash Cherumannil; Prasad, S. Krishna; Prasad, Bhagavatula L. V. (ChemPhysChem, 2025)
Modification of the intrinsic hydrophilic character of the pristine silica nanoparticles (SiNP) decorated with silanol moieties into a hydrophobic state has been of substantial interest, owing to the amenability to gelation of desirable liquids. Many reports exist on composites of SiNP with liquid crystals (LCs), an epitome of anisotropic soft matter. The fumed SiNP, unlike its precipitated counterpart, has been the preferred variety. A family of colloidal gel systems is reported, consisting of precipitated SiNP in a nematic LC, formed by substituting some native silanols with methyl, butyl, or dodecane chains. Detailed steady state and oscillatory rheological measurements are performed, along with analyses using the soft glass and other viscoelastic models. The study demonstrates that the sophisticated modified fractional models, Kelvin-Voight and Maxwell, proposed for generalized viscoelastic behavior of soft materials, are quite successful in describing these nematic gels as well. The observed nontrivial relationship between the ligand length and the strength of the gel network is elucidated on the basis of a judicious combination of the van der Waals, hydrogen bonding, and hydrophobic interactions, leading to a detailed understanding of the viscoelastic behavior of the composites and the influence of SiNP surface chemistry.
Keywords: fractional viscoelastic models; Hydrophobic; nematic; rheological studies; silica nanoparticles

Vastly increased mesophase range due to superstructure formation from in situ prepared gold nanoparticles with liquid crystalline ligands: toward enhanced optoelectronic applications - Duggal, Muskan; Khatavi, Santosh; Yelamaggad, Channabasaveshwar V.; Shankar Rao, Doddamane Sreenivasamurthy; Krishna Prasad, Subbarao; Prasad, Bhagavatula L. V. (ACS Applied Nano Materials, 2025)
Gold nanoparticle (Au NP)-liquid crystal (LC) composites have gained considerable interest in developing cutting-edge electro-optical materials. This study introduces an innovative synthetic approach that significantly augments the capabilities of Au NP-LC composites by utilizing an amine-functionalized LC as both a reducing and capping agent in the refined Brust-Schiffrin method. In its standard form, this method yields Au NP-LC composites with appealing features like improved clearing temperature. However, the optical characteristics do not display any additional features and resemble simple LC-ligand functionalized Au NP, attributed here to the surplus LC employed to obtain the dual capabilities of reduction and capping. Thus, it was gratifying to observe a dramatic enhancement in mesophase stability with the removal of just a few percentages of excess LC, which is attributed to a remarkable and unprecedented one-dimensional superstructure formation. Furthermore, the removal of surplus LC caused the composite to exhibit Fano-like resonance in the UV-vis spectrum, a noteworthy optical feature likely resulting from dynamic plasmonic interactions, including plasmon-polariton interactions and lattice plasmon modes. Thus, the simple yet robust protocol employed yields Au NP-LC composites with an ultrawide thermal range of the mesophase that paves the way for realizing next-generation electro-optic materials featuring enhanced performance and response.
Keywords: Fano-resonance; gold nanoparticles; liquid crystals; nanosoftcomposites; superstructure

Self-powered photodetection in AgBiS2 nanocrystals synthesized from AgBi-mixed-metal thiolate - Das, Mouli; Swathi, S. P.; Prasad, Bhagavatula L. V. (ACS Applied Nano Materials, 2026)
AgBiS2 has emerged as a promising optoelectronic material owing to its high absorption coefficient, environmentally friendly and abundant components, offering a sustainable alternative to lead- and cadmium-based chalcogenides. Realizing the full potential of AgBiS2 devices, however, requires scalable synthesis routes that include development of suitable precursors and minimize the use of harsh solvents, elevated temperatures, inert environments, etc. Here, we present a facile, solvent-free synthesis of phase pure AgBiS2 nanocrystals (NCs) at room temperature and under ambient conditions, enabled by the AgBi mixed-metal thiolate (AgBi-MMT) precursor complex. The initial choice of metal salts determines the nature of the metal thiolate intermediate complex, which subsequently influences the quality of the resulting AgBiS2 NCs. As a single-source precursor of the metals, AgBi-MMT enables controlled release of Ag+ and Bi3+ ions, yielding phase-pure AgBiS2 NCs. Furthermore, the MMT that is derived from AgI and BiI3 precursors promotes in situ surface passivation of the AgBiS2 NCs by iodide ions by trapping molecular I2 within its matrix. Under illumination, these iodide ions undergo reversible migration, generating a built-in potential and enabling self-powered photodetection in devices prepared from the as-synthesized NCs. This work expands the synthesis methodology of AgBiS2, highlighting the importance of metal thiolates as precursors in nanomaterial syntheses, and influence of iodine species in photo-operational devices.
Keywords: built-in potential; iodine; ion migration; layered; quantum dots